Perbaikan Tahanan Pentanahan dengan Menggunakan Bentonit Teraktivasi - Devy Andini; Yul Martin; Herri Gusmedi (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2016)
Intisari — Salah satu hal yang mempengaruhi tahanan pentanahan adalah tahanan jenis tanah. Tahanan jenis tanah dipengaruhi oleh beberapa hal yaitu struktur tanah, temperatur, pengaruh kandungan air (kelembaban), dan pengaruh kandungan kimia dalam tanah. Dalam penelitian ini untuk menurunkan tahanan pentanahan dilakukan penambahan bentonit kedalam tanah, tetapi sebelum digunakan bentonit terlebih dulu diaktivasi. Tujuan dari penelitian ini adalah untuk Mengetahui perubahan besar tahanan pentanahan yang diberikan bentonit yang belum teraktivasi dan sudah teraktivasi. Pentanahan yang diberikan bentonit teraktivasi memiliki nilai tahanan pentanahan lebih kecil dibandingkan saat diberikan bentonit yang belum teraktivasi. Persentasi perubahan bentonit yang telah teraktivasi yaitu sebesar 79,97%-85,24% sedangkan persentasi perubahan tahanan pentanahan saat diberikan bentonit yang belum teraktivasi sebesar 22,84%-85,25%. Kata kunci — Tahanan pentanahan, tahanan jenis tanah, aktivasi bentonit Abstract — One of the things that affect the grounding resistance is soil resistivity. Soil resistivity is influenced by several things: the structure of the soil, the temperature, the influence of the water content (moisture), and the effect of chemical constituents in the soil. In this research to lose custody grounding the addition of bentonite into the ground, but before use bentonite first in activation. The aim of this study is to know the major changes grounding given bentonite which has not been activated and has been activated .Grounding were given activated bentonite has a grounding resistance value is smaller than when given bentonite which has not been activated .Percentage changes that have been activated bentonite in the amount of 79,97%-85,24% whereas the percentage change in resistance grounding when given bentonite which has not been activated by 22,84%-85,25%. Keywords— Grounding, Soil Resistivity, Activation of bentonite